Sodium glucose co-transporter 2 inhibitors in patients with resistant hypertension: a case study. (August 2016) - Obeid, Amira; Pucci, Mark; Martin, Una; Hanif, Wasim
Sodium glucose co-transporter 2 inhibitors lower blood pressure by osmotic diuresis and can be considered in diabetic patients with resistant hypertension.